Feature Selection and Classification of Type II Diabetes on High Dimensional Dataset - Vinoth, Priya (Qeios, 2024)
Information mining is a methodology of bringing huge models utilizing recorded information. It is normally utilized in different real applications to be express web records, double dealing distinctive confirmation talk attestation, human organizations, and so forth. Reenacted insight includes are utilized in information mining to imagine the future occasion subject to the models conveyed utilizing solid information. All the highlights got during information assortment may not be altogether important to the objective class of the model. Highlight choice is a system which picks the best subset of highlights in dataset to upgrade the demonstration of an information mining or AI estimation. As of now, observational assessment is driven on Naïve Bayesian classifier utilizing Pima Indian Type II Diabetes dataset with all the highlights what's more the subset of the highlights picked by predefined python libraries. The presentation of Naïve Bayesian classifier is assessed on all of things to come subset of the dataset to consider the effect of the high dimensionality on the presentation of Naïve Bayes Classifier.